Pengembangan Model Pembelajaran Berbasis Riset untuk Peningkatan Keterampilan Berpikir Kreatif dan Keterampilan Kolaboratif pada Mahasiswa Program Studi Pendidikan IPS - Ardiansyah, Andri Noor; Arif, Muhamad; Bahar, Syairul; Alfarauq, Farkhan Abdurochim (Sosio-Didaktika: Social Science Education Journal, 2025)
The aim of this research is: To obtain an overview of the research-based learning development and implementation model to improve creative thinking skills and collaborative skills in students of the Social Sciences Education Study Program. The research method that will be used is a qualitative method with a descriptive approach. The subjects in this research were IPS students from the Class of 2022 and 2023 who took Physical Geography and Indonesian Regional Geography courses for one semester. Data collection techniques include observation, interviews, literary studies and questionnaires. The research results state that the implementation of student research learning is through observation/practicum activities which aim to be a means of thinking innovatively, connecting theory with practice, and producing ideas that are relevant to social challenges. This is integrated with the Semester Learning Plan (RPS) for several courses by allowing students to go out into the field as a condition for passing courses. The results of the observations/practicum are in the form of activity reports that are recorded, video reports that are uploaded to the study program's YouTube, and published in several scientific journals.